Fundraising for social change - Klein, Kim (Hoboken, New Jersey : John Wiley & Sons, 2016)
Annotation The bible of grassroots fundraising, updated with the latest tools and methods"Fundraising for Social Change" is the preeminent guide to securing funding, with a specific focus on progressive nonprofit organizations with budgets under $5 million. Used by nonprofits nationally and internationally, this book provides a soup-to-nuts prescription for building, maintaining, and expanding an individual donor program. Author Kim Klein is a recognized authority on all aspects of fundraising, and this book distills her decades of expertise into fundraising strategies that "work." This updated seventh edition includes new information on the impact of generational change, using social media effectively, multi-channel fundraising, and more, including expanded discussion on retaining donors and on legacy giving. Widely considered the 'bible of grassroots fundraising, ' this practically-grounded guide is an invaluable resource for anyone who has to raise money for important causes. A strong, sustainable fundraising strategy must possess certain characteristics. You need people who are willing to ask and realistic goals. You need to gather data and use it to improve results, and you need to translate your ideas in to language donors will understand. A robust individual donor program creates stable and long-term cash flow, and this book shows you how to structure your fundraising appropriately no matter how tight your initial budget. Develop and maintain a large base of individual donors Utilize strategies that pay off sooner rather than later Expand your reach and get your message out to the donor pool Translate traditional fundraising methods into strategies that work for social justice organizations with little or no front moneyBasing your fundraising strategy on the contributions of individual donors may feel like herding cats--but it's the best way for your organization to maintain maximum freedom to pursue the mission that matters. A robust, organized, planned approach can help you reach your goals sooner, and "Fundraising for Social Change" is the field guide for putting it all together to make big things happen
What's new, what's hot, what's over, what's not. Nonprofits and the money they raise ; Creating a fundraising philosophy ; Be clear about what the money will do ; What you have to understand to begin fundraising ; The importance of a good board of directors -- Ask them, thank them, ask them again. Financial needs and fundraising strategies ; Thank before you bank ; Getting comfortable with asking ; Ask a real prospect ; How to ask ; Strengthening relationships by creating categories of donors -- Strategies for acquisition and retention. Multi-channel fundraising ; What successful mass appeals have in common ; Direct mail ; Online fundraising ; Using the telephone ; Special events ; Establishing voluntary fees for service ; Door-to-door and street canvassing ; Opportunistic fundraising -- Inviting current donors to make bigger gifts. Building major donor programs ; Setting up and maintaining recurring donor programs ; Legacy giving ; Setting up an endowment -- Using a campaign strategy for raising large amounts of money. What all large campaigns have in common ; Raising money for capital ; Endowment campaigns ; Conducting feasibility studies -- Budgeting and planning. Developing a budget ; Creating a fundraising plan ; The perennial question of clean and dirty money ; What to do in case of financial trouble -- Fundraising management. Infrastructure for fundraising ; Hiring a development director ; Using a consultant, coach, mentor, or trainer ; Dealing with anxiety -- You the fundraiser. Know what you need to know ; Working with your executive director ; Working with volunteers ; When you encounter ethical dilemmas -- Special circumstances. Raising money in rural communities ; Fundraising for a coalition ; When no one is paid ; When you are just starting out.
Includes bibliographical references and index.
Print version record.
John Wiley and Sons
Keywords: Fund raising -- United States; Nonprofit organizations -- United States -- Finance; Collecte de fonds; Associations sans but lucratif -- x; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare; SOCIAL SCIENCE -- Human Services; Fund raising; Nonprofit organizations -- Finance; United States; Spendensammlung; Nonprofit-Organisation; Finanzierung; USA